Elimination of polar micropollutants and anthropogenic markers by wastewater treatment in Beijing, China. (January 2015) - Qi, Weixiao; Singer, Heinz; Berg, Michael; Müller, Beat; Pernet-Coudrier, Benoit; Liu, Huijuan; Qu, Jiuhui
Highlights: The studied wastewater facilities are representative for large cities in China. The occurrence, elimination efficiency, and per-capita loads were assessed. Pollutant patterns were similar as in Europe, including caffeine and sucralose. Total per capita pollutant loads are currently lower than in Western countries. Wastewater used directly for irrigation poses a threat to soils and food safety. Abstract: Anthropogenic contamination of surface waters in Asia is on the increase. While polar organic contaminants are gradually recognized for their impacts on aquatic ecosystems in the Western World, less is known about the situation in Asia. In developing countries like China, water resources are particularly vulnerable. We investigated the occurrence, elimination, and per capita loads of a wide range of pharmaceuticals, household chemicals and pesticides in five Beijing WWTPs representative for megacities in China, and compare the efficiency of different treatment processes. Based on initial screening for 268 micropollutants using high-resolution mass spectrometry, 33 compounds were examined in detail. Pollutant concentrations in raw wastewater ranged from <0.02 μg L −1 for pesticides to >20 μg L −1 for caffeine and the contrast agent iopromide. Concentrations in the WWTP effluents were generally <1 μg L −1, except for some pharmaceuticals, iopromide (1.2–18 μg L −1 ), caffeine (0.025–2.3 μg L −1 ), and the artificial sweetener sucralose (2.7–3.5 μg L −1 ). Elimination efficiencies varied greatly from <1% to close to 100%, with macrolides, some sulfonamides, metronidazole, iopromide, and 4-acetamidoantipyrine being the most persistent compounds. Total per capita loads of the investigated micropollutants were lower than in communal wastewater of Europe, amounting to 7.9–12.2 and 2.0–6.5 g d −1  1000 inhabitants −1 in the influents and effluents, respectively, with an average release of ∼100 kg d −1 by the 11.4 million people and 2.3 million m 3 of wastewater treated per day. Since the wastewater effluents are often used for agricultural irrigation, residual organic pollutants pose a threat to food safety, the development of antibacterial resistance, and combined effects of micropollutants in the aquatic environment.